Návrh na zlepšení konkurenceschopnosti firmy pomocí marketingových nástrojů - Adámková, Pavla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce se zabývá problematikou návrhu marketingové strategie, která by měla vést k zisku nových zákazníků, udržení stávajících zákazníků a dále k většímu zisku, na základě teoretických poznatků a analýzy současného stavu firmy.

The Master’s thesis deals with the proposal of marketing strategy, which should lead to gain new costumers, maintaining the existing costumers and a higher profits, based ontheoretical knowledge and analysis of contemporary conditions of the company.
Proposal for an Improvement of Company Competitiveness by Marketing Tools
Keywords: Marketing; marketingový mix; produkt; cena; místo; propagace; SLEPT analýza; Porterův model; 7S; SWOT analýza.; Marketing; marketing mix; product; price; place; promotion; SLEPT analysis; Porter model; 7S; SWOT analysis.